Graph Coloring on the Primary Dryland Forest Cover Map of Kalimantan Using the Greedy Algorithm - Izzaty Farha; Putri Pita Mutia; Rachel Cornelia Simanjuntak; Desi Febriani Putri; Fidia Deny Tisna Amijaya (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
In graph theory, graph coloring is a popular approach, including in map creation, and this study aims to apply the Greedy algorithm to color forest land-cover maps while ensuring that adjacent areas do not share the same color. The data used consist of land-cover classification maps and the relationships between regions represented as planar graphs. The Greedy algorithm is implemented by arranging nodes based on their highest degrees and then coloring them sequentially. The coloring results show that the algorithm can provide an efficient solution with a minimum number of colors according to the upper bound of graph coloring, particularly for primary dry forest land-cover maps in East Kalimantan Province, achieving a chromatic number χ(G) = 4, ensuring no neighboring areas share the same color. Although it does not always yield an optimal solution, the algorithm proves effective, simple, and applicable to various other uses such as spatial analysis, regional clustering, or geographic information systems. The novelty of this study lies in its application to primary dry forests in Kalimantan, which have been rarely explored, and its contribution to spatial analysis and conservation efforts.